Septic Stability? Gut Microbiota in Young Adult Mice Maintains Overall Stability After Sepsis Compared to Old Adult Mice. Issue 4 (April 2021) - Mankowski, Robert T.; Thomas, Ryan M.; Darden, Dijoia B.; Gharaibeh, Raad Z.; Hawkins, Russell B.; Cox, Michael C.; Apple, Camille; Nacionales, Dina C.; Ungaro, Ricardo F.; Dirain, Marvin L.; Moore, Fredrick A.; Leeuwenburgh, Christiaan; et al.
ABSTRACT: Background: Older adults have worse outcomes after sepsis than young adults. Additionally, alterations of the gut microbiota have been demonstrated to contribute to sepsis-related mortality. We sought to determine if there were alterations in the gut microbiota with a novel sepsis model in old adult mice, which enter a state of persistent inflammation, immunosuppression, and catabolism (PICS), as compared with young adult mice, which recover with the sepsis model. Methods: Mixed sex old (∼20 mo) and young (∼4 mo) C57Bl/6J mice underwent cecal ligation and puncture with daily chronic stress (CLP+DCS) and were compared with naive age-matched controls. Mice were sacrificed at CLP+DCS day 7 and feces collected for bacterial DNA isolation. The V3–V4 hypervariable region was amplified, 16S rRNA gene sequencing performed, and cohorts compared. α-Diversity was assessed using Chao1 and Shannon indices using rarefied counts, and β-diversity was assessed using Bray-Curtis dissimilarity. Results: Naive old adult mice had significantly different α and β-diversity compared with naive adult young adult mice. After CLP+DCS, there was a significant shift in the α and β-diversity (FDR = 0.03 for both) of old adult mice (naive vs. CLP+DCS). However, no significant shift was displayed in the microbiota of young mice that underwent CLP+DCS in regards to α-diversity (FDR = 0.052) and β-diversity (FDR = 0.12), demonstrating a greater overall stability of their microbiota at 7 days despite the septic insult. The taxonomic changes in old mice undergoing CLP+DCS were dominated by decreased abundance of the order Clostridiales and genera Oscillospira. Conclusion: Young adult mice maintain an overall microbiome stability 7 days after CLP+DCS after compared with old adult mice. The lack of microbiome stability could contribute to PICS and worse long-term outcomes in older adult sepsis survivors. Further studies are warranted to elucidate mechanistic pathways and potential therapeutics.